“Information And Communication Technologies For Indigenised Development In Borneo: Towards The Post-​2015 Sustainable Agenda” - Universiti Malaysia Sarawak, Institute of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak (UNIMAS), 2015)
Professor Dr. Roger Harris, a visiting professor at ISITI, recently spoke on the topic “Information and Communication Technologies for Indigenised Development in Borneo: Towards the Post-​2015 Sustainable Agenda”.